Spooky riddles - Brown, Marc Tolon (New York : Beginner Books, 1983)
Witches, skeletons, ghosts, vampires, mummies, and the like are featured in this collection of riddles.
Keywords: Riddles, Juvenile; Supernatural -- Juvenile humor; Riddles; Supernatural -- Wit and humor